Biodiesel-triple bottom line (TBL): A new hierarchical sustainability assessment framework of principles criteria & indicators (PC&I) for biodiesel production. Part II-validation. (October 2016) - Bautista, S.; Enjolras, M.; Narvaez, P.; Camargo, M.; Morel, L.
Highlights: A new framework for the sustainability assessment of biodiesel is validated. Validation strategy based on expert consultations and statistical analysis were developed. The framework consists of dimensions, principles, criteria and indicators (PC&I). Identification of potential groups between PC&I was represented by data visualization techniques. The framework proposed could be adapted and applied to biodiesel production in specific contexts. Abstract: Sustainability assessment is a critical issue for the biodiesel production chain. The constant growth of the biodiesel industry has generated important sustainability concerns, such as competition with food production, indirect land use change, and impacts on water, biodiversity and social values. Government policies consider that quantitative, robust and independent sustainability assessment is vital to estimate the extent to which the biodiesel industry impacts sustainability issues. However, weaknesses in the definition of adequate indicators to measure the sustainability of biodiesel production have been identified. In this context, this work proposes a hierarchical assessment framework based on sustainability dimensions, principles, criteria and indicators. To do this, after a systematic literature review, a first version of the framework was proposed. Then, to define the final framework, a validation strategy based on expert survey consultations and a descriptive statistical analysis were developed. In order to define the principles and criteria importance for sustainability assessment of biodiesel, 62 experts answered an online survey assessing three attributes: relevance, ease of measurement and reliability. The first result of the validation analysis was the definition of a framework composed of five dimensions (social, economic, environmental, political and technological), 13 principles, and 30 criteria that would be part of a sustainability assessment of biodiesel production. The second result was the identification of potential groups and relationships between principles and criteria represented through data visualization techniques. The validated framework provides the basis for defining future studies about interdimensional principles and criteria. Also, the proposed sustainability assessment framework could be adapted and applied to biodiesel production in specific contexts.